Railroads for Michigan - Meints, Graydon M. (Book collections on Project MUSE., 2013)
This book tells the story of the railroad's arrival and development in Michigan. The author describes the long-awaited and often-troubled advent of the railroad in the state, the building of which shifted from private to public efforts and back again, amid tumultuous social, business, and political developments. The railroad would come to play a role in almost every critical event in Michigan's history, including the Civil War, the Granger Movement, and the Gilded Age, before beginning to wane following the arrival of the automobile, the Interstate Commerce Commission, World War I, and the Great Depression. A brief growth spurt during World War II was short-lived, and it was followed by the collapse of several major railroads and the formation of Amtrak and Conrail. Looking ahead to the future of the railroad in the Great Lakes region, the author assesses the strengths and shortcomings of this revolutionary invention.